1973
DOI: 10.1017/s0033291700054313
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte membrane cation carrier in depressive illness

Abstract: SynopsisErythrocyte sodium concentration, potassium concentration, Na-K ATPase activity, and ouabain sensitive potassium influx were determined in female inpatients suffering from a depressive illness. In most patients the biochemical values were also determined shortly before the patient's discharge from hospital. The Na-K ATPase and the ouabain sensitive potassium influx increased significantly with improvement in the depressive mood rating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

1975
1975
1997
1997

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(54 citation statements)
references
References 17 publications
2
52
0
Order By: Relevance
“…The small changes are difficult to interpret in view of the large variance in the data but they suggest that lithium treatment only causes an increase in Na/K ATPase activity when there is an associated recovery of the patients. This is supported by the finding that amelioration of mood is correlated with increased Na/K ATPase activity (Naylor et al, 1973). Lithium itself may not cause any change in erythrocyte membrane Na/K ATPase activity.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…The small changes are difficult to interpret in view of the large variance in the data but they suggest that lithium treatment only causes an increase in Na/K ATPase activity when there is an associated recovery of the patients. This is supported by the finding that amelioration of mood is correlated with increased Na/K ATPase activity (Naylor et al, 1973). Lithium itself may not cause any change in erythrocyte membrane Na/K ATPase activity.…”
Section: Discussionmentioning
confidence: 78%
“…The majority of the lithium-treated group had recovered and so it was not possible to separate drug and recovery effects in this case. Erythrocyte sodium concentration has been shown to decrease following recovery from depressive illness not associated with lithium treatment (Naylor, McNamee & Moody, 1971, Naylor et al, 1973 whereas recovery from depression following lithium treatment has been found to be associated with an increase in erythrocyte sodium concentration (Mendels, Frazer, Secunda & Stoken, 1971;Mendels & Frazer, 1974-however this was not confirmed by Mendels, Frazer & Secunda, 1972). Our results show lithium treatment to be associated with an increase in both the erythrocyte sodium concentration and erythrocyte membrane Na/K ATPase activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Biochemical studies of erythrocytes and platelets have demonstrated an altered activity of the cation transport enzyme, sodium + potassium activated adenosine triphosphatase (the sodium pump), in unipolar depression and in the depressed and manic phases of bipolar illness (Naylor et al 1973(Naylor et al , 1974aSengupta et al 1980;Akagawa et al 1980). Some studies have shown a normalization of these changes following clinical recovery or after treatment with lithium salts (Hokin-Neaverson et al 1976;Naylor et al 19746, 1977).…”
Section: Studies Of Cation Transportmentioning
confidence: 99%